The criteria of maximal dissipativity and self-adjointness for a class of differential-boundary operators with bounded operator coefficients - Storozh, O. G.; Pipa, H. M. (Methods of Functional Analysis and Topology, 2008)
A class of the second order differential-boundary operators acting in the Hilbert space of infinite-dimensional vector-functions is investigated. The domains of considered operators are defined by nonstandard (e.g., multipoint-integral) boundary conditions. The criteria of maximal dissipativity and the criteria of self-adjointness for investigated operators are established.